THE USE OF INFORMATION GAP TECHNIQUE IN TEACHING FLUENCY IN SPEAKING - Sari, Jamila; Sofian, Sofian; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to answer the research question â€œis the use of information gap techniqueeffective to increase studentsâ€™ fluency in speaking?â€ The researcher focused on the eleventh grade students of Madrasah Aliyah Raudhatul Ulum Meranti in Academic Year 2016/2017 by administering a spoken test of asking and giving opinion before and after the treatments. In conducting this research, the researcher applied a-Quasi Experimental Study with provide two groups; experimental group and control group. The population of this research was all students on eleventh grade and the sample was taken from class A (28 students) and class B (28 students).Â The data were calculated and the result showed that the score of studentsâ€™ post-test in experimental group (43.285) was higher than score of studentsâ€™ post-test in control group (35.357) in conclusion, it is clear that the use of information gap technique effect on increasing studentsâ€™ fluency in speaking. Therefore, the Null Hypothesis that says â€œthere is no difference between the students achievementin increasing fluency in speaking using Information Gap Technique and without using Information Gap Techniqueâ€was rejected, and the Alternative Hypothesis that says â€œthere is significant different between studentsâ€™ achievement increasing fluencyÂ in speaking using Information Gap Technique and without using Information Gap Techniqueâ€ was accepted.Â Keywords: A-Quasi Experimental study, fluency, information gap technique, speaking